Assessing the Impacts and Costs of Forced Displacement : Volume 1. A Mixed Methods Approach - Fiddian-Qasmiyeh, Elena; Ruiz, Isabel; Vargas-Silva, Carlos; Zetter, Roger (World Bank, Washington, DC, 2013)
Globally, over 40 million people have been forced to leave or flee their homes due to conflict, violence, and human rights violations either as refugees outside their country of origin or Internally Displaced Persons (IDPs). A substantial number live in protracted displacement where return has not been possible.Forced displacement is a humanitarian crisis: but it also produces developmental impacts - short and longer term, negative and positive - affecting human and social capital, economic growth, poverty reduction efforts, environmental sustainability and societal fragility. A prevailing view is that refugees are a burden on the development aspirations of host countries and populations and that negative socio-economic and environmental impacts and costs outweigh the positive contributions (actual or potential) that forcibly displaced people might make. The losses incurred by the displaced populations themselves reinforce perceptions of vulnerability and dependency and thus assumptions of the burden they might impose. This study provides such a methodology. The development and drafting of the methodology and the state of the art literature review was conducted by the refugee studies centre, with valuable and constructive inputs from the partner organizations.